2017
DOI: 10.1371/journal.pone.0185568
|View full text |Cite
|
Sign up to set email alerts
|

Lotus japonicus alters in planta fitness of Mesorhizobium loti dependent on symbiotic nitrogen fixation

Abstract: Rhizobial bacteria are known for their capacity to fix nitrogen for legume hosts. However ineffective rhizobial genotypes exist and can trigger the formation of nodules but fix little if any nitrogen for hosts. Legumes must employ mechanisms to minimize exploitation by the ineffective rhizobial genotypes to limit fitness costs and stabilize the symbiosis. Here we address two key questions about these host mechanisms. What stages of the interaction are controlled by the host, and can hosts detect subtle differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 74 publications
3
44
0
Order By: Relevance
“…While plants had similar numbers of nodules and equivalent nodule weights across three nitrogen levels, we found that the amount of viable rhizobia hosted in host cells varied. Control of rhizobial fitness within nodules has been shown in legumes, most recently in L. japonicus, in which there is evidence that plants can differentially control fitness of effective and ineffective rhizobia within a single nodule (Quides et al, 2017). Similarly, sanction strength-meaning the ability to control rhizobial fitness in individual nodules-was also predicted (West et al, 2002) and shown (Kiers et al, 2006) to increase with addition of external nitrate in soybeans.…”
Section: Discussionmentioning
confidence: 98%
“…While plants had similar numbers of nodules and equivalent nodule weights across three nitrogen levels, we found that the amount of viable rhizobia hosted in host cells varied. Control of rhizobial fitness within nodules has been shown in legumes, most recently in L. japonicus, in which there is evidence that plants can differentially control fitness of effective and ineffective rhizobia within a single nodule (Quides et al, 2017). Similarly, sanction strength-meaning the ability to control rhizobial fitness in individual nodules-was also predicted (West et al, 2002) and shown (Kiers et al, 2006) to increase with addition of external nitrate in soybeans.…”
Section: Discussionmentioning
confidence: 98%
“…In the legume–rhizobia symbiosis, plant hosts preferentially allocate resources and influence relative rhizobial fitness in response to differences in N 2 fixation among nodules, a process often called “host sanctions.” Host effects on differential resource allocation and relative rhizobial fitness (as measured by differences in nodule size and number of rhizobial cells per nodule, respectively) have been observed widely (e.g., Kiers, Rousseau, West, & Denison, 2003; Simms et al., 2006; Heath & Tiffin, 2009; Oono, Anderson, & Denison, 2011; Regus, Gano, Hollowell, & Sachs, 2014; but see Gubry‐Rangin, Garcia, & Béna, 2010). However, these effects have not been observed as well among nodules that differ only moderately in nitrogen‐fixation rate or efficiency (but see Heath & Tiffin, 2009; Kiers, Rousseau, & Denison, 2006; Quides, Stomackin, Lee, Chang, & Sachs, 2017) nor under alternative environmental conditions, such as nitrate additions (but see Regus et al, 2014; Wendlandt et al, 2019). Even fewer studies have explored how strains that only differ moderately in mutualistic quality are sanctioned under varying environmental conditions (but see Kiers et al., 2006; Regus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prior strategies to mitigate the RCP have largely focused on promoting infection by rhizobia in elite inoculants (Santos et al 2019), but direct competition for shared host resources can extend competition beyond infection (stage 1) and into persistence (stage 2). Host control mechanisms are predicted to be sufficient to select against sub-optimal rhizobia, but in some cases, rhizobia that extract a disproportionate amount of resources can persist within host tissue (Gano-Cohen et al 2016;Kiers et al 2006;Quides et al 2017;Sachs et al 2010;Zgadzaj et al 2015). By limiting the energetic output for nitrogen fixation, rhizobia can increase host resource consumption for their own reproduction (Trainer and Charles 2006).…”
Section: Hyper-competitive Inoculum Approachmentioning
confidence: 99%